The effect of autostereoscopic holograms on anatomical knowledge: a randomised trial. Issue 11 (21st October 2018) - Hackett, Matthew; Proctor, Michael
Abstract : Context: Three‐dimensional (3‐D) visualisation in anatomical education has been shown to be broadly beneficial for students. However, there is limited research on the relative efficacy of 3‐D modalities. This study compares knowledge performance, mental effort and instructional efficiency between autostereoscopic 3‐D visualisation (holograms), monoscopic 3‐D visualisation (3‐DPDFs) and a control (2‐D printed images). Methods: A cardiac anatomy model was used to generate holograms, 3‐DPDFs and 2‐D printed images. Nursing student participants ( n = 179) were randomised into three groups: holograms ( n = 60), 3‐DPDFs ( n = 60) and printed images ( n = 59). Participants completed a pre‐test followed by a self‐study period using the anatomical visualisation. Afterwards, participants completed the NASA‐Task Load Index (NASA‐TLX) cognitive load instrument and a knowledge post‐test. Results: Post‐test results showed participants studying with holograms (median = 80.0, interquartile range [IQR] = 66.7–86.7) performed significantly better regarding cardiac anatomy knowledge than participants using 3‐DPDF (median = 66.7, IQR = 53.3–80.0, p = 0.008) or printed images (median = 66.7, IQR = 53.3–80.0, p = 0.007). Mental effort scores, on a scale from 1 to 20, showed hologram (mean = 4.9, standard deviation [SD] = 3.56) and 3‐DPDF participants (mean = 4.9, SD = 3.79) reported significantly lower cognitive load than printed images (mean = 7.5, SD = 4.9, p < 0.005). Instructional efficiency ( E ) of holograms ( E = 0.35) was significantly higher than printed images ( E = −0.36, p < 0.001), although not significantly higher than 3‐DPDF ( E = 0.03, p = 0.097). Conclusions: Participants using holograms demonstrated significant knowledge improvement over printed images and monoscopic 3‐DPDF models, suggesting additional depth cues from holographic visualisation provide benefit in understanding spatial anatomy. Mental effort scores and instructional efficiency of holograms indicate holograms are a cognitively efficient instructional medium. These findings highlight the need for further study of novel 3‐D technologies and learning performance. Abstract : Hackett and Proctor use holograms to demonstrate the importance of depth when striving to learn spatial anatomy